2022
DOI: 10.3389/fpsyt.2022.842609
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Breakthroughs in Targeting the Oxytocin System to Treat Alcohol Use Disorder

Abstract: Development of better treatments for alcohol use disorder (AUD) is urgently needed. One promising opportunity for this development is the potential of targeting the oxytocin peptide system. Preclinical studies showed that administration of exogenous oxytocin or, more recently, stimulation of neurons expressing endogenous oxytocin lead to a decreased alcohol consumption across several rodent models. Initial clinical studies also showed that administration of oxytocin decreased craving for alcohol and heavy alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 98 publications
(132 reference statements)
0
2
0
Order By: Relevance
“…Preclinical studies have shown that oxytocin attenuates drug-seeking behaviors and reduces drug reward in animal models of addiction [64]. Studies have explored the use of oxytocin in the treatment of alcohol, cocaine, heroin, and opioid dependence, with some evidence suggesting reductions in drug cravings and relapse rates [65,66,67].…”
Section: Therapeutic Potential Of Oxytocinmentioning
confidence: 99%
“…Preclinical studies have shown that oxytocin attenuates drug-seeking behaviors and reduces drug reward in animal models of addiction [64]. Studies have explored the use of oxytocin in the treatment of alcohol, cocaine, heroin, and opioid dependence, with some evidence suggesting reductions in drug cravings and relapse rates [65,66,67].…”
Section: Therapeutic Potential Of Oxytocinmentioning
confidence: 99%
“…A reduction of craving and alcohol consumption may only be detectable shortly after oxytocin administration, as suggested by one rodent study ( Stevenson et al, 2017 ). Despite these failures, oxytocin may still have considerable potential in the treatment of alcohol use disorder if pharmacokinetic problems can be solved ( Ryabinin and Zhang, 2022 ), or if oxytocin could find use as an “as needed” medication for rapid reduction of alcohol consumption.…”
Section: Off-label Medication For Relapse Prophylaxismentioning
confidence: 99%